2014
DOI: 10.1080/08870446.2014.942663
|View full text |Cite
|
Sign up to set email alerts
|

Profiling patient attitudes to phosphate binding medication: A route to personalising treatment and adherence support

Abstract: Objective: Nonadherence to phosphate binding medication (PBM) compromises the efficacy of treatment for chronic kidney disease (CKD), but its causes are poorly understood. This study sought to explore patient attitudes towards PBM and to evaluate the utility of the Necessity-Concerns Framework for understanding adherence to PBM. Design: A sample of two hundred and twenty-one dialysis patients currently prescribed PBM were surveyed from eight UK renal units. Main Outcome Measures: Demographic data and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…44,48,49 Dietary intake patterns in our own unit have confirmed this strong trend. Phosphate binder medication, traditionally prescribed to be taken "with meals" now should be directed to times of higher food intake.…”
Section: Accept the Fact That Patients Often Do Not Eat Three Traditisupporting
confidence: 61%
See 2 more Smart Citations
“…44,48,49 Dietary intake patterns in our own unit have confirmed this strong trend. Phosphate binder medication, traditionally prescribed to be taken "with meals" now should be directed to times of higher food intake.…”
Section: Accept the Fact That Patients Often Do Not Eat Three Traditisupporting
confidence: 61%
“…It has also been estimated that adherence to binder use as prescribed may be less than 50%. [44][45][46][47][48][49] Recent research has shown that phosphorus absorption varies among foods. Current nutrition advice in phosphate control is moving toward a greater understanding by both patients and health care teams on newly understood mechanisms of phosphate content and absorption.…”
Section: Phosphorus Binders and Food Absorption Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for PB non‐adherence may include overall treatment non‐adherence, lower socioeconomic status, or lack of understanding of likely benefits of lower SPhos . Another possible reason is a high pill burden.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for PB non-adherence may include overall treatment non-adherence, lower socioeconomic status, or lack of understanding of likely benefits of lower SPhos. [24][25][26] Another possible reason is a high pill burden. Consistent with other observational studies, we show a trend toward an association (unadjusted P = 0.01, adjusted P = 0.15) between higher PB pill burden and patient-reported PB non-adherence.…”
Section: Hemodialysis International 2015; ••:••-••mentioning
confidence: 99%